The Use of Very Low Concentrations of High‐sensitivity Troponin T to Rule Out Acute Myocardial Infarction Using a Single Blood Test. (7th September 2016) - Body, Richard; Mueller, Christian; Giannitsis, Evangelos; Christ, Michael; Ordonez‐Llanos, Jorge; de Filippi, Christopher R.; Nowak, Richard; Panteghini, Mauro; Jernberg, Tomas; Plebani, Mario; Verschuren, Franck; French, John K.; et al.
Abstract: Background: Recent single‐center and retrospective studies suggest that acute myocardial infarction (AMI) could be immediately excluded without serial sampling in patients with initial high‐sensitivity cardiac troponin T (hs‐cTnT) levels below the limit of detection (LoD) of the assay and no electrocardiogram (ECG) ischemia. Objective: We aimed to determine the external validity of those findings in a multicenter study at 12 sites in nine countries. Methods: TRAPID‐AMI was a prospective diagnostic cohort study including patients with suspected cardiac chest pain within 6 hours of peak symptoms. Blood drawn on arrival was centrally tested for hs‐cTnT (Roche; 99th percentile = 14 ng/L, LoD = 5 ng/L). All patients underwent serial troponin sampling over 4–14 hours. The primary outcome, prevalent AMI, was adjudicated based on sensitive troponin I (Siemens Ultra) levels. Major adverse cardiac events (MACE) including AMI, death, or rehospitalization for acute coronary syndrome with coronary revascularization were determined after 30 days. Results: We included 1, 282 patients, of whom 213 (16.6%) had AMI and 231 (18.0%) developed MACE. Of 560 (43.7%) patients with initial hs‐cTnT levels below the LoD, four (0.7%) had AMI. In total, 471 (36.7%) patients had both initial hs‐cTnT levels below the LoD and no ECG ischemia. These patients had a 0.4% ( n = 2) probability of AMI, giving 99.1% (95% confidence interval [CI] = 96.7% to 99.9%) sensitivity and 99.6% (95% CI = 98.5% to 100.0%) negative predictive value. The incidence of MACE in this group was 1.3% (95% CI = 0.5% to 2.8%). Conclusions: In the absence of ECG ischemia, the detection of very low concentrations of hs‐cTnT at admission seems to allow rapid, safe exclusion of AMI in one‐third of patients without serial sampling. This could be used alongside careful clinical assessment to help reduce unnecessary hospital admissions.